Pemerolehan Bahasa dan Budaya Indonesia Penutur Asing melalui Cerita Rakyat - Fajria Noviana (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2018)
This paper aims to explain the effectiveness of the use of teaching materials in the form of folklore for foreign speakers of Indonesian language, in an effort to gain knowledge about the language and culture of Indonesia. The learning method of Indonesian for foreign speakers, known as BIPA, used is direct method because the class is heterogeneous. In addition to the acquisition of four language skills, which are listening, reading, speaking, and writing; foreign speakers of Indonesian as a learner also managed to get five of the seven cultural elements as proposed by Koentjaraningrat. These five cultural elements are language, knowledge systems, social systems or social organizations, living or technology equipment systems, and living systems of livelihood. Therefore, I assumed that the use of folklore or other literary works can be continued and developed as teaching materials in BIPA’s learning.